The Effect of Understanding Taxation, Justice, Discrimination, Tax Rates, Taxation Systems, Tax Sanctions on Student Perceptions of Tax Evasion - Ica Novita Anggareni; Mujiyati Mujiyati (International Journal of Economics and Management Research, 2024)
This study aims to analyze the effect of understanding taxation, justice, discrimination, tax rates, taxation systems, tax sanctions on student perceptions of tax evasion. This research method is quantitative. The data collection technique used by researchers in this study was a questionnaire method. The population in this study were students majoring in Accounting at Universitas Muhammadiyah Surakarta. The sampling technique in this study was to use purposive sampling method. The data source used by this researcher is primary data. Data analysis techniques through statistical analysis. SPSS. The results of this study are that tax understanding has no effect on student perceptions of tax evasion, high or low understanding of taxation will not affect tax evasion. Justice has no effect on student perceptions of tax evasion, high or low justice will not affect tax evasion. Discrimination affects students' perceptions of tax evasion, the higher the discrimination by the government, the more ethical tax evasion is considered. Conversely, the lower the discrimination, the tax evasion is considered an unethical thing to do. Tax rates have no effect on student perceptions of tax evasion, high or low tax rates will not affect tax evasion. The tax system affects students' perceptions of tax evasion, the better the tax system, the tax evasion is considered an unethical act. Conversely, the lower the tax system, the more ethical tax evasion is considered. Tax sanctions have no effect on student perceptions of tax evasion, high or low tax sanctions will not affect tax evasion.